The main problems that affect english students when learning and using phrasal verbs: case of the students of 3° year of the Major of Modern Languages Specialty in French and English at the Foreign Language - Chevez Hernández, Andrea; Pinto Amaya, Karla Beatriz; Velásquez Herrera, Orfa Yaneth (2024)
The research team through the investigation identified, classified and analyzed the most common factor that affects the acquisition and usage of Phrasal Verbs to student; since thought the year Phrasal Verbs have been a very difficult part of the learning process of English. The results showed that the most common Phrasal Verbs are those that were not necessarily taught in the course of Phrasal Verbs, but those that were learned because of their frequent usage in the English language.